PENGUKURAN KINERJA RANTAI PASOK DENGAN INTEGRASI METODE SUPPLY CHAIN OPERATION REFERENCE (SCOR) DAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) DI PT. KUNANGO JANTAN - Henny Yulius; Riko Ervil; Della Yulina Novita (Sekolah Tinggi Teknologi Industri Padang, 2022)
PT. Kunango Jantan is a manufacturing industry that focuses on the distribution of ready-to-use steel plates for the construction, mining, electricity, telecommunication and transportation industries. In the procurement process there were delays in raw materials, which affected production time which resulted in not achieving production volume targets and delays in delivery. In the production process there are several obstacles so that the product is not in accordance with the wishes of the customer. This resulted in consumer dissatisfaction with the company. So that in this study the measurement of the company's supply chain performance must be carried out. This study uses the Supply Chain Operation Reference (SCOR) method with the integration of the Analytical Hierarchy Process (AHP) method. The SCOR method is used to determine supply chain performance and the AHP method is used to determine the weighting of performance indicators.The results of SCOR are that there are 6 core processes that are carried out at PT. Kunango Jantan, namely plan, source, make, deliver, return and enable. Then with 24 measurement matrices obtained, which consists of 3 performance attributes, namely reliability, responsiveness and agility. The plan process is the highest priority with a value of 26 and for the measurement matrix the highest value is the manage performance of return processes cycle with a value of 0.115. Return is the lowest core process of 1.166 and Schedule Defective Return Receipt Cycle Time The is the lowest performance matrix with a value of 0.06 and these two lowest processes require more attention for improvement of all processes that must be continuously evaluated.